A finite strain chemo-poro-mechanical framework for the chemically stimulated permeation of fluid in polymer gels. (December 2022) - Shi, Yuhao; Wallmersperger, Thomas
Polyelectrolyte polymer gels can significantly increase or decrease their volume by an external stimulus. The reason for this ability is the multiphasic structure of the gel. In the present work, a chemo-electro-poromechanical model is presented, which is supposed to map the swelling behavior of chemically stimulated polymer gels. The presented model was implemented in COMSOL Multiphysics ®, and the swelling behavior of an acrylamide gel was simulated afterward. The mechanical parameters were obtained from experimental data using a least square optimization while the other material parameters were calibrated to the experimentally determined swelling behavior.